Bakhtinian’s carnivalesque in Angela Carter’s The Magic Toyshop, several perceptions, nights at the circus and wise children - Shima Sadat Mirmusa (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
It is on the tradition of the postmodern and magical realist texts to be in the business of liberating from conventions and established norms and blurring the borders. The way in which these subversive texts challenge the traditionally accepted codes and regulations is directly allied to Bakhtin’s notion of the carnivalesque through which the firmly established hierarchical laws of the society are inverted. The paper convincingly argues how Carter’s fiction, an influential paradigm of magical realism, erodes the boundaries of the paradoxical impulses and celebrates the confusion of the categories through incorporating the theories of carnivalisation. It suggests the ways in which carnivalesque operates to open the possibilities to construct a dehierarchized world which is deprived of privileged sectors, patriarchal authority and any form of supremacy and is filled with the primacy of marginality.